Implementasi Kebijakan Pemberdayaan Perempuan Dalam Pembangunan di Kecamatan Motoling Barat Kabupaten Minahasa Selatan - Binilang, Angle; Rumapea, Patar (JURNAL ILMU ADMINISTRASI (JIA), 2013)
Abstract: This study is to determine how the implementation of the policy of women empowerment, khsusnya programs / activities SPP-PNPM Mandiri in the district. The method used in this study is a qualitative method. The focus of the research is the implementation of policies and the results of policy implementation SPP / the SPP program. Source of research data is PNPM actors at the district level (district government, UPK PNPM Mandiri, and district facilitators) and PNPM actors at the village level, the overall total of 18 people . Collecting data using interview techniques. The analysis technique used is the qualitative analysis of interactive model of Miles and Hubermann. The results provide conclusion: (1) Implementation of the empowerment of women in development policies in the district of West Motoling through SPP-PNPM Rural in general has done well and correctly in accordance with the procedures and mechanisms that have been established. (2) The implementation of women's empowerment in development policy in the district of West Motoling through SPP-PNPM results and positive impact on women, especially women of poor households (RTM) to increase the potential and ability in improving the economic condition of the family, and also impact on the progress of the development of rural economies in the village savings and loan activities are managed by women. Based on this research are suggested: (1) women's empowerment in development policy through SPP-PNPM Mandiri, should be continued and enhanced implementation. (2) The allocation of funds for the PNPM Mandiri SPP activities specified maximum of 25% of the PNPM Mandiri district funds, need to be considered to be improved, (3) Local Government should allocate more funds from the budget adequate to support programs to empower women of poor households. Keywords: policy implementation, empowerment